PROSES KELUAR MASUK BAHAN BAKU PEMBUATAN TAS DI PERUSAHAAN KOREA PADA DIVISI GUDANG PT. KOMITRANDO EMPORIO - , JEANNE .A.A. TUWONAUNG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This graduating paper entitled â The Process of In and Out of Raw Materials in Producing Bags of Warehouse Division at Korean Company PT. KomitrandoEmporioâ aims to describe the process of in and out and handling the raw materials at warehouse division of PT. KomitrandoEmporio. Through the research conducted by collecting data and interviewing one of the company staffs discovers that the process of in and out of raw materials at warehouse division of PT. KomitrandoEmporio is divided into three steps